HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN REGULASI DIRI SISWA DI SMP NEGERI 16 KOTA JAMBI - Aniza Novalia Putri; Yanto Yanto; Muhammad Alridho Lubis (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The aim of this research is to determine the relationship between peer conformity and student self-regulation at SMP Negeri 16 Jambi City. This study uses a quantitative approach with correlational research methods. The population in this study were students in grades VII and VIII at SMP Negeri 16 Jambi City. The sampling technique in this study used stratified random sampling so that a total sample size of 250 students was obtained. The data analysis technique was carried out by descriptive analysis, statistical assumptions, and correlation with the product moment method. The results showed that there was a significant relationship between peer conofmity and student self-regulation. The results of the analysis with a significant value of 0.000 <0.05 with the acquisition of r count 0.332 which is interpreted as a low correlation. The results of the study are positive which means that the higher the level of peer conformity, the higher the level of student self-regulation and vice versa, the lower the level of peer conformity, the lower the student self-regulation